Ciptaningrasa Bojongan Sebagai Bentuk Prototype Edukasi Visual - Lalan Ramlan; Jaja Jaja (Universitas Sultan Ageng Tirtayasa, 2023)
Jaipongan by Gugum Gumbira has become a separate dance genre, has four types of movements as dance constructions, among others; bukaan, pencugan, nibakeun, and mincid used in each dance repertoire. The dance construction has high elasticity or flexibility, because there is no set stiffness. However, in the dynamics of its development outside of Jugala production, it is increasingly losing its entity, because background dances with Jaipongan nuances are often called Jaipongan dances. In connection with this, the problems raised in the research of works of art with the title